Hubungan Motivasi Belajar dengan Hasil Belajar Siswa di SMK Negeri 7 Kota Bandung - Dede (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
Learning outcomes have an important role in the learning process. Learning outcomes are used to determine the extent to which students can understand and understand the material provided. There are so many aspects that affect learning outcomes, including motivation. The purpose of this study is to determine the relationship between learning motivation and student learning outcomes. This study used a quantitative approach with a correlative descriptive method. This study was conducted with questionnaires and test results on 30 respondents (students) SMKN 7 Bandung City. As for the processing and analysis of data with statistical analysis techniques SPSS V. 25. The results of the study, showed, that: There is a positive and significant and linear relationship with the value of Sig. (2-tailed) between the Learning motivation variable and the learning outcome variable of 0.000 < 0.05 then H0 is rejected and Ha is accepted which means there is a significant correlation relationship between the two variables.